2022
DOI: 10.1093/molbev/msac210
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Bai-Yue Ancestry in Aboriginal Li People on Hainan Island

Abstract: As the most prevalent aboriginal group on Hainan Island located between South China and the mainland of Southeast Asia, the Li people are believed to preserve some unique genetic information due to their isolated circumstances, although this has been largely uninvestigated. We performed the first whole-genome sequencing of 55 Hainan Li (HNL) individuals with high coverage (∼30–50×) to gain insight into their genetic history and potential adaptations. We identified the ancestry enriched in HNL (∼85%) is well-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 122 publications
7
19
0
Order By: Relevance
“…All F2517 lineages were observed in Li people, which was consistent with a recent whole-genome sequencing study [55]. Chen et al found O1b1a1a was the dominant lineage in southern East Asians, which diverged from others 10998 years ago, and the F2517 sublineages were further divided into O1b1a1a1a1b2a1a1a and O1b1a1a1a1b2a1a1b clades at 2828 years ago [55]. Sun et al also found most sublineages of M119, including our identi ed F1759, Z23420 and Z23266, contributed to the ancient gene pool of modern Tai-Kadai, Austronesian and southern Han Chinese [10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All F2517 lineages were observed in Li people, which was consistent with a recent whole-genome sequencing study [55]. Chen et al found O1b1a1a was the dominant lineage in southern East Asians, which diverged from others 10998 years ago, and the F2517 sublineages were further divided into O1b1a1a1a1b2a1a1a and O1b1a1a1a1b2a1a1b clades at 2828 years ago [55]. Sun et al also found most sublineages of M119, including our identi ed F1759, Z23420 and Z23266, contributed to the ancient gene pool of modern Tai-Kadai, Austronesian and southern Han Chinese [10].…”
Section: Discussionsupporting
confidence: 91%
“…Sublineages of O1b1a1a1a1b2a1a1-F2517 (23), O1b1a2a1-F1759 (10), O1a1a1b-Z23420 (15) and O1a1a2a1a-Z23266 (11) had undergone population expansion recently. All F2517 lineages were observed in Li people, which was consistent with a recent whole-genome sequencing study [55]. Chen et al found O1b1a1a was the dominant lineage in southern East Asians, which diverged from others 10998 years ago, and the F2517 sublineages were further divided into O1b1a1a1a1b2a1a1a and O1b1a1a1a1b2a1a1b clades at 2828 years ago [55].…”
Section: Discussionsupporting
confidence: 78%
“…Sublineages of O1b1a1a1a1b2a1a1-F2517 (23), O1b1a2a1-F1759 (10), O1a1a1b-Z23420 (15) and O1a1a2a1a-Z23266 (11) had undergone population expansion recently. All F2517 lineages were observed in Li people, which was consistent with a recent whole-genome sequencing study [64]. Chen et al found O1b1a1a was the dominant lineage in southern East Asians, which diverged from others 10998 years ago, and the F2517 sublineages were further divided into O1b1a1a1a1b2a1a1a and O1b1a1a1a1b2a1a1b clades at 2828 years ago [64].…”
Section: Discussionsupporting
confidence: 82%
“…All F2517 lineages were observed in Li people, which was consistent with a recent whole-genome sequencing study[64]. Chen et al found O1b1a1a was the dominant lineage in southern East Asians, which diverged from others 10998 years ago, and the F2517 sublineages were further divided into O1b1a1a1a1b2a1a1a and O1b1a1a1a1b2a1a1b clades at 2828 years ago[64]. Sun et al also found most sublineages of M119, including our identified F1759, Z23420 and Z23266, contributed to the ancient gene pool of modern Tai-Kadai, Austronesian and southern Han Chinese[10].We could also identify the shared paternal lineages among Li, southern Han and Gelao people in the distribution of M119 mutations.…”
supporting
confidence: 91%
“…We collected population data from all different HM ethnicity identities, which included the Miao Large-scale high-coverage WGS projects aiming at East Asians, including the ChinaMAP, NyuWa genomic resources, and other single population admixture history reconstructions focused on Li, Tibetan, Hui and others [5,6,47,48], have provided insights into fine-scale genetic stratification, genetic diversity, dispersal, and admixture landscape. However, HM-speaking populations were a significant lack in the early genomic projects, which are essential for better understanding the genetic diversity of South China and Mainland Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%